Essays on the impact of conflict on household welfare in Nigeria - Atilola, Bolanle (Kansas State University, 2024)
The farmer-herder conflict has escalated in Nigeria in recent years, causing detrimental impacts on agriculture, livelihoods, and human welfare. However, limited research exists on how this conflict affects children's health and nutrition in Nigeria. This dissertation aims to bridge the gap in the literature by estimating the causal impact of conflict on households' nutrition and health outcomes, as well as income. We assessed how the impact of conflict differs by conflict timing, geographical regions, and sub-population groups. In the first chapter, we employ a difference-in-differences approach using data obtained from the 2018 Nigeria Demographic and Health Survey and Armed Conflict Location and Event Dataset to analyze the impact of farmer-herder conflict exposure on children's anthropometric outcomes. Our findings, while not showing a general impact of conflict exposure on children's anthropometric outcomes, reveal a significant and heterogeneous impact on children living in farm households when using a triple difference model. Findings reveal that conflict significantly reduces weight-for-age and height-for-age Z-scores of exposed farm household children by 2.14 and 2.43 standard deviations, respectively, indicating increased underweight and stunting conditions. However, we find no statistically significant impact of conflict on weight-for-height Z-scores. The second chapter analyzes the impact of farmer-herder conflict on crop income in Nigeria. Using panel data from the Nigeria General Household Survey (2010-2016) and geo-referenced conflict data, we implement a panel fixed effects model exploiting spatial and temporal variation in conflict events. Results reveal that exposure to conflict events within 10km does not have a statistically significant impact on crop income. This finding is robust at different levels of conflict exposure. Further analysis shows no differential impact across different phases of the agricultural cycle.
Keywords: Conflict; Difference-in-difference; Panel fixed effects model; Anthropometric score; Crop income; Triple difference